APLIKASI KAMUS ONLINE KATA INDONESIA KE KATA JAWA KRAMA DAN KATA JAWA KRAMA KE KATA INDONESIA - Uro Abdulrohim; Dani Pradana Kartaputra; Danuri Adi Pengestu (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2019)
For some people who want to learn Indonesia Javanese Krama, it may be difficult. Seldom find Javanese Krama-Indonesian dictionary, well documented in book form or electronically, because it is needed the means to facilitate every person who wants to learn and understand the language of the Javanese Krama well. From what has been described, then is was made a Java application Krama-Indonesian dictionary-based website. The application is made by using the programming language PHP (Hypertext Preprocessor) and DBMS (Database Management System) that is used is MySQL. In this application there are features such as translation feature, login features and some of the features that support this application to be easy to use. For addition information on this application there is also information about Javanese culture in Yogyakarta. With this application, it is sufficient to answer the user wishes to learn the Java language Krama.